1994
DOI: 10.1080/01688639408402631
|View full text |Cite
|
Sign up to set email alerts
|

Calculation and number processing: Assessment battery; role of demographic factors

Abstract: This paper describes the structure and contents of EC301, a standardized testing battery for the evaluation of brain-damaged adults in the area of calculation and number processing. The battery was administered to 180 normal subjects stratified by education (3 levels), age (3) and gender. EC301 is composed of a large variety of tasks dealing with basic arithmetic skills, and their linguistic, spatial, and mnesic dimensions. The three main notational systems for numbers--Arabic digits, written verbal, and spoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…Prior studies 3,25 that investigate the correlation between age and calculation report that age did not display any significant role on calcu-lation or in terms of processing speed. These findings coincide with those in the present study as noted in Table 4, in which no differences were observed between ages of individuals in the group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies 3,25 that investigate the correlation between age and calculation report that age did not display any significant role on calcu-lation or in terms of processing speed. These findings coincide with those in the present study as noted in Table 4, in which no differences were observed between ages of individuals in the group.…”
Section: Discussionmentioning
confidence: 99%
“…It consists of multifactorial processes, including verbal and spatial abilities, memory and executive functions 1 . realization of mathematical calculations can be impaired in cases of cerebral dysfunction and/or injuries [2][3][4][5][6] as well as in dementias 7,8 . The loss of the ability to perform calculation tasks resulting from a cerebral pathology is known as acalculia or acquired dyscalculia.…”
mentioning
confidence: 99%
“…Language and speech was assessed using the Aachener Aphasie test (AAT; Huber et al, 1983), a language battery comprising a 5-point rating scale for spontaneous speech, and five subtests, the token-test, oral repetition, written language, confrontation naming, and comprehension. Arithmetical functions were assessed using a reduced form of the EC301 battery (Deloche et al, 1994). This standardized assessment battery covers arithmetical and numerical skills like counting, enumeration, number transcoding, evaluation of quantities, access to arithmetical facts and algorithms for written operations; the Graded Difficulty Arithmetic Test (GDAE; Jackson and Warrington, 1986) was used to test the ability to perform mental additions and subtractions of increasing difficulty under time pressure.…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
“…His number processing and calculation abilities were assessed initially with a calculation battery that had many similarities in terms of concept and methodology with the NPC battery (Delazer et al 2003) or EC301 test (Deloche et al 1994)-Battery 1. This test included the following tasks: counting (by 1 and by 7), dots counting, transcoding (reading Arabic numbers, reading number words, writing numbers to dictation, writing Arabic numbers to dictation, transcoding Arabic numerals into number words, transcoding number words into Arabic numerals), number comparison (comparing Arabic numbers and comparing written number words), recognition of number signs, simple arithmetic (requiring to the patient to provide an oral response to one-digit additions, multiplications, one-to two-digit subtractions and simple divisions), mental calculation (necessitating an oral response to up to two-digit additions, subtractions and up to 3-digit multiplications and divisions), complex written calculation (asking the patient to provide a written response to complex operations with up to 3-digit numbers), cardinality estimation (positioning Arabic and word numbers on a vertical scale that extended from 0 at the bottom to 100 at the top), approximation (asking the patient to chose the answer that he considered to be the closest correct result to an complex operation from a group of 4 false results), contextual magnitude judgment (e.g., to indicate whether a number of objects represent a small, medium or large quantity in a given context), time estimation (e.g., how long ago the current president was elected) general number knowledge (e.g., how many months are in a year) and personal number knowledge (e.g., his date of birth).…”
Section: Methodsmentioning
confidence: 99%